2011
DOI: 10.1007/s11596-011-0586-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study on expression of GST-π protein in brain tissue and peripheral blood of epilepsy rats induced by pilocarpine

Abstract: Previous studies have suggested that glutathione-S-transferase π (GST-π) over-expression in the brain tissue is associated with refractory epilepsy. However, whether the change in GST-π level in the peripheral blood is in line with that in brain tissue remains unknown. This study examined the correlation between GST-π in brain tissue and that in peripheral blood in rat models of pilocarpine-induced refractory epilepsy. The animals were divided into drug-resistant group and drug-responsive group according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Still, expression of GSTP1 was found to be significantly higher in brain specimens from patients with epilepsy, than in controls [11]. Furthermore, Deng et al have found that the change in expression of GSTP in peripheral blood shows the same pattern as that in brain tissues, suggesting GSTP might contribute to drug resistance in epilepsy, suggesting that the GSTP over-expression in peripheral blood could be used as a marker for resistance to anti-epileptic agents [31].…”
Section: Discussionmentioning
confidence: 99%
“…Still, expression of GSTP1 was found to be significantly higher in brain specimens from patients with epilepsy, than in controls [11]. Furthermore, Deng et al have found that the change in expression of GSTP in peripheral blood shows the same pattern as that in brain tissues, suggesting GSTP might contribute to drug resistance in epilepsy, suggesting that the GSTP over-expression in peripheral blood could be used as a marker for resistance to anti-epileptic agents [31].…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior evidence of changes in glutathione‐ S ‐transferase π (GSTP) protein expression levels in the epileptic brain, Deng et al [] measured changes in both brain (by quantitative immunohistochemistry) and blood (by Western blotting) in response to pilocarpine‐induced epilepsy in rats. As hypothesized, levels of GSTP were significantly higher in the drug‐resistant group than in the drug‐responsive group, while no significant difference was found between the control and the drug‐responsive groups.…”
Section: Comparability Of the Proteomementioning
confidence: 99%